Compound Heterozygosity for Novel Truncating Variants in the LMOD3 Gene as the Cause of Polyhydramnios in Two Successive Fetuses - Wang, Ye; Zhu, Caixia; Du, Liu; Li, Qiaoer; Lin, Mei-Fang; Férec, Claude; Cooper, David N.; Chen, Jian-Min; Zhou, Yi (Frontiers in Genetics, 2019)
Polyhydramnios is sometimes associated with genetic defects. However, establishing an accurate diagnosis and pinpointing the precise genetic cause of polyhydramnios in any given case represents a major challenge because it is known to occur in association with over 200 different conditions. Whole exome sequencing (WES) is now a routine part of the clinical workup, particularly with diseases characterized by atypical manifestations and significant genetic heterogeneity. Here we describe the identification, by means of WES, of novel compound heterozygous truncating variants in the LMOD3 gene [i.e., c.1412delA (p.Lys471Serfs*18) and c.1283dupC (p.Gly429Trpfs*35)] in a Chinese family with two successive fetuses affected with polyhydramnios, thereby potentiating the prenatal diagnosis of nemaline myopathy (NM) in the proband. LMOD3 encodes leiomodin-3, which is localized to the pointed ends of thin filaments and acts as a catalyst of actin nucleation in skeletal and cardiac muscle. This is the first study to describe the prenatal and postnatal manifestations of LMOD3-related NM in the Chinese population. Of all the currently reported NM-causing LMOD3 nonsense and frameshifting variants, c.1412delA generates the shortest truncation at the C-terminal end of the protein, underscoring the critical role of the WH2 domain in LMOD3 structure and function. Survey of the prenatal phenotypes of all four known LMOD3-related severe NM cases served to identify fetal oedema as a novel presenting feature that may provide an early clues for to facilitate prenatal diagnosis of the disease.